Choppy water - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2020)
"Stone Barrington and his friends are vacationing in Maine when their leisure is suddenly disrupted by extreme weather. To make matters worse, the inclement conditions allow for a menacing adversary to sneak in unnoticed and deliver a chilling message. Soon it becomes clear that the target of the incident is one of Stone's closest companions, and that these enemies have a grander scheme in mind. From the bustling streets of New York City to the sun-drenched shores of Key West, Stone intends to nab the criminals that appear behind him at every step. But his search only leads him further down a trail of peril and corruption, and he'll soon find that at the end of the road is a more dangerous foe than he could have imagined.."--